2017
DOI: 10.1016/j.ijsu.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

High BMI and male sex as risk factor for increased short-term renal impairment in living kidney donors – Retrospective analysis of 289 consecutive cases

Abstract: Obese donors do not suffer from an increased risk of intraoperative or perioperative complication rates. However, male sex and high BMI are associated with a more pronounced short-term decline in renal function. The impact of BMI on long-term consequences for kidney donors needs to be defined in larger prospective cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
1
9
1
2
Order By: Relevance
“…In addition, we found no significant differences between HARP and LDN in terms of operative outcome, postoperative outcome and postoperative kidney function except for blood loss. [5,6,12]. Our institute is one of the largest centers in living kidney donation and transplantation in Western Europe, therefore the beneficial effect of hospital volumes might result in better outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found no significant differences between HARP and LDN in terms of operative outcome, postoperative outcome and postoperative kidney function except for blood loss. [5,6,12]. Our institute is one of the largest centers in living kidney donation and transplantation in Western Europe, therefore the beneficial effect of hospital volumes might result in better outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Part of that workup includes an analysis of the patient's BMI. There have been conflicting studies regarding the association between donor BMI and postoperative renal compromise [1][2][3][4][5][6][7][8]. Motivated by these conflicting studies, we examine the association of kidney MAP score with postoperative renal function in healthy donors.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study also incorporates these concepts in the examination of long term renal function in a cohort of patients undergoing HALDN. Additionally, age and male sex have previously been correlated with decreased postoperative donor renal function [3,23]. By definition, the MDRD 2006 equation correlates age, sex, and race with eGFR because these variables are included in the calculation of eGFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unger et al reported short-term outcomes following donor nephrectomy in obese versus non-obese donors [49]. In a retrospective analysis of 289 Austrian kidney donors who underwent nephrectomy between 2006 and 2015, 126 donors had a BMI ≤ 25 kg/m 2 , 120 had a BMI between 25 and 30 kg/ m 2 and 43 had a BMI ≥ 30 kg/m 2 .…”
Section: Obese Donorsmentioning
confidence: 99%